Microbial fuel cells: a green and alternative source for bioenergy production - Al-Gheethi, Adel; Ali Noman, Efaq; A. Talip, Balkis; Radin Mohamed, Radin Maya Saphira (Springer Nature, 2020)
Microbial fuel cell (MFC) represents one of the green technologies for the production of bioenergy. MFCs using microalgae produce bioenergy by converting solar energy into electrical energy as a function of metabolic and anabolic pathways of the cells. In the MFCs with bacteria, bioenergy is generated as a result of the organic substrate oxidation. MFCs have received high attention from researchers in the last years due to the simplicity of the process, the absence in toxic by-products, and low requirements for the algae growth. Many studies have been conducted on MFC and investigated the factors affecting the MFC performance. In the current chapter, the performance of MFC in producing bioenergy as well as the factors which inﬂuence the efﬁcacy of MFCs is discussed. It appears that the main factors affecting MFC’s performance include bacterial and algae species, pH, temperature, salinity, substrate, mechanism of electron transfer in an anodic chamber, electrodes materials, surface area, and electron acceptor in a cathodic chamber. These factors are becoming more inﬂuential and might lead to overproduction of bioenergy when they are optimized using response surface methodology (RSM).